A novel system integrating water electrolysis and supercritical CO2 cycle for biomass to methanol. (5th May 2023) - Zhang, Qijun; Chen, Heng; Li, Bo; Pan, Peiyuan; Xu, Gang; Zhao, Qinxin; Jiang, Xue
Highlights: Novel design integrating biomass gasification with methanol synthesis. Syngas from gasification are mixed with hydrogen from the electrolytic cell for methanol synthesis. The waste heat will be fed into the supercritical CO2 cycle for power generation. A high waste-to-electricity efficiency can be achieved. A short payback period can be excepted with plenty of financial revenues. Abstract: In order to improve the efficiency of conventional biomass to methanol, a novel cogeneration system is designed that couples an electrolytic water subsystem with a s-CO2 cycle and a conventional biomass to methanol system. The novel cogeneration system uses syngas converted from biomass gasification and hydrogen obtained by water electrolysis for methanol synthesis, and it uses a supercritical CO2 cycle to improve its performance. The proposed process was modeled and calculated using Aspen Plus and MATLAB as the main simulation software to analyze its energy efficiency, exergy efficiency and economics, and to illustrate the advantages of the system compared with the conventional biomass to methanol system from a thermodynamic point of view. Taking a biomass with a mass flow rate of 2.78 kg/s for example, the energy efficiency of the new process was increased by 19.89% for the same biomass consumption conditions. The results show that the system has an energy efficiency of 67.98% and an exergy efficiency of 64.82%. The irreversibility comes from two main components: the gasifier and the electrolyzer. The project is expected to achieve a net present value of 22, 948, 830 over its 20-year life cycle.